1990
DOI: 10.1037/0882-7974.5.1.3
|View full text |Cite
|
Sign up to set email alerts
|

Dementia and agitation in nursing home residents: How are they related?

Abstract: The link between agitated behaviors and cognitive functioning in 408 nursing home residents was examined. Results showed that cognitively impaired residents manifested aggressive behaviors (e.g., cursing, hitting) and physically nonaggressive behaviors (e.g., pacing). The highest levels of physically nonaggressive behaviors were manifested by those residents who presented intermediate levels of impairment in their performance of activities of daily living. Cognitively intact residents exhibited verbally agitat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
101
0
4

Year Published

1996
1996
2016
2016

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 144 publications
(108 citation statements)
references
References 12 publications
3
101
0
4
Order By: Relevance
“…Previous research in the nursing home and day care populations showed a much clearer relationship of increase in agitation with cognitive decline for physically nonaggressive behaviors as well as for aggressive behaviors in comparison with verbal nonaggressive behaviors (8,11). We therefore examined the time course of each syndrome for three levels of cognitive impairment based on the baseline score of the BCRS: cognitively intact; BCRS 1-2 (n = 27); moderate impairment; 3-5 (n = 43); and severe impairment; 6-7 (n = 34); These are presented in Figures 2-5.…”
Section: Does Cognitive Functioning Explain the Longitudinal Change Imentioning
confidence: 99%
“…Previous research in the nursing home and day care populations showed a much clearer relationship of increase in agitation with cognitive decline for physically nonaggressive behaviors as well as for aggressive behaviors in comparison with verbal nonaggressive behaviors (8,11). We therefore examined the time course of each syndrome for three levels of cognitive impairment based on the baseline score of the BCRS: cognitively intact; BCRS 1-2 (n = 27); moderate impairment; 3-5 (n = 43); and severe impairment; 6-7 (n = 34); These are presented in Figures 2-5.…”
Section: Does Cognitive Functioning Explain the Longitudinal Change Imentioning
confidence: 99%
“…Patients with cognitive impairment are more prone to aggressive behavior and wandering than those with milder impairment, who show more verbal agitated behaviors. However, this is observed mainly in institutions 23 . A recent nine year prospective study on the relationship between cognition and BPSD in a community sample of demented patients failed to show such tendencies.…”
Section: Discussionmentioning
confidence: 91%
“…This is reflected in the reductions on physiological stress measures seen in the QP group. Losses in social functioning associated with dementia can result in the person with dementia feeling alone and furthermore, when living in a LTC facility, their connection with others may be influenced by the environment, limited staffing and visitors, [2][3][4] as well as by the stigmatization of their disease. 27 Social connections are important 28 and can improve psychological well-being.…”
Section: Discussionmentioning
confidence: 99%
“…Predisposing factors are related to internal features such as personality and functional and cognitive impairment, and external features including characteristics of the environment. 2 The anxiety associated with unfamiliar surroundings, the disorientation and mental confusion, and the social isolation that accompanies dementia can often create increased stress for people living in long-term care (LTC) settings. 3 Such a response is thought to affect the autonomic nervous system and result in emotional and physical symptoms of distress, 4 and as a result the individual can experience a stress response.…”
mentioning
confidence: 99%